Audit Opinions and Experiences Impact on Decision of Credit Analyst - Artie Arditha Rachman; Endang Asliana (Politeknik Negeri Lampung, 2013)
The aim of the research is to do empirical examination about the role of independent auditor opinion and credit analysts’ experience to the credit decision. Previous research had shown that audit opinion made by independent auditor influenced the decision made by credit analysts. Other research also shown that experience influenced the decision making process. Combining the two factors, this research shows the results supporting previous research. Each independent variables shows that the effect of audit opinion and credit analysts’ experience is statistically significant to the decision made by credit analysts’. The interaction between both variables also exists in this research.Key word: decision making, audit report, experience